Decay of solutions of a system of nonlinear Klein-Gordon equations - José Ferreira; Gustavo Perla Menzala (International Journal of Mathematics and Mathematical Sciences)
We study the asymptotic behavior in time of the solutions of a system of nonlinear Klein-Gordon equations. We have two basic results: First, in the L∞(ℝ3) norm, solutions decay like 0(t−3/2) as t→+∞ provided the initial data are sufficiently small. Finally we prove that finite energy solutions of such a system decay in local energy norm as t→+∞.